Musical instruments in Nepali sculpture - Poudel, Parsuram Prasad (Journal of Fine Arts Campus, 2022)
Nepal is rich in fine arts. Within the fine arts, music and sculpture have an interdependent relationship because of the various religions, cultures, festivals, and traditional practices, that have been existing since ancient times. As a result, varieties of musical instruments can be seen in some of the sculptural works such as metal, stone, and wood sculptures that the ancestors carved out and installed in the various temple courtyards. The main purpose of this article is to interpret and analyze, only the string instruments (Tantri V dya), that have been carved in Nepali sculptures. To solve the query, some temple areas in the Kathmandu Valley have been visited to find out the sculptures carved along with musical instruments. From the study, it has been found that some tantri v dya, such as veena and other string instruments which are played using the bow, were seen played by various religious and mythological characters. Likewise, the instrument playing style and posture were also found in many manners. The present study is more focused on only the string instruments in sculptures rather than their historical background. Thus, future researchers will be get precise guide to study about others musical instruments too. Although the research is carried out within a limited time and area, the present paper appears to be relevant and fruitful for all the readers.